Photoelectrocatalytic oxidation of methanol over RuO2MnO2Co3O4 supported porous anatase under visible light irradiation - Che Mat, Ahmad Nazeer; Sairi, Nor Asrina; Basirun, Wan Jefrey; Rezayi, Majid; Mat Teridi, Mohammad Asri; Mazhar, Muhammad (Elsevier, 2019)
Anatase supported heterogeneous photocatalyst consisting of RuO2, MnO2 and Co3O4 (1:13:13 ratio) was synthesized by a precipitation method and tested for photoelectrocatalytic (PEC) oxidation of methanol in 0.1 M KOH under visible light irradiation. The as-prepared photocatalyst was characterized by FTIR, UV–vis, XRD, Raman spectroscopy, FESEM/EDX, TEM, BET, XPS and TPR. The PEC studies by cyclic voltammetry indicated that the oxidation of methanol to CO2 and H2O upon exposure to visible light occurs between 400 and 800 nm. The smaller value of the charge transfer resistance (Rct) of the RuO2–MnO2–Co3O4 supported anatase TiO2 electrode indicates a faster rate of charge transfer at the electrode-electrolyte interface compared to the Pt/C catalyst, which could be promising for direct methanol fuel cell application.